2017
DOI: 10.7150/ijms.20962
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Treatment Improves Diabetic Retinopathy by Alleviating Autophagy through GLP-1R-ERK1/2-HDAC6 Signaling Pathway

Abstract: Objective: Apoptosis and autophagy of retinal cells, which may be induced by oxidative stress, are tightly associated with the pathogenesis of diabetic retinopathy (DR). The autophagy induced by oxidative stress is considered as excessively stimulated autophagy, which accelerates the progression of DR. This study aims to investigate the protective effect of GLP-1 treatment on alleviating apoptosis and autophagy of retinal cells in type 2 diabetic rats and reveals its possible mechanism.Methods: Type 2 diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…The results indicated that exendin-4 pretreatment attenuated the hIAPP-induced increase in the LC3II/I ratio and decrease in p62 expression, both of which are indicators of autophagy. Previous studies have demonstrated that GLP-1 exerts protective effects by inhibiting excessive autophagy (10,34,35). All of these studies, taken together with the present results, suggest that exendin-4 may exhibit protective effects by attenuating hIAPP-induced autophagy in MIN6 cells.…”
Section: Discussionsupporting
confidence: 83%
“…The results indicated that exendin-4 pretreatment attenuated the hIAPP-induced increase in the LC3II/I ratio and decrease in p62 expression, both of which are indicators of autophagy. Previous studies have demonstrated that GLP-1 exerts protective effects by inhibiting excessive autophagy (10,34,35). All of these studies, taken together with the present results, suggest that exendin-4 may exhibit protective effects by attenuating hIAPP-induced autophagy in MIN6 cells.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we investigated the role of the histone deacetylase HDAC6 in the early events characterizing the progression of an experimental model of DR. Dysregulation of the processes of acetylation/deacetylation of nuclear and cellular proteins has been shown to be associated with different pathologic conditions including diabetes [12][13][14][15][16][17][18]23]. Previous findings linked the activity of several histone deacetylases to the pathogenesis of DR [23,24]. A specific contribution of HDAC1, 2, and 8 to global acetylation of retinal histones in the diabetic retina was found to be involved not only to progression of DR but also to the metabolic memory phenomenon [23].…”
Section: Discussionmentioning
confidence: 93%
“…While the specific role of HDAC6 in the diabetic retina has not been studied before, HDAC6 inhibition has been shown to alleviate myocardial ischemia-reperfusion injury in diabetic rats [16] and to ameliorate diabetic kidney disease [15], predominantly through antioxidant effects. Interestingly, in the diabetic retina, downregulation of HDAC6 was linked to the effects of exogenous GLP-1 in alleviating oxidative stress-induced apoptosis and autophagy of retinal cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…And the administration of liraglutide ameliorated metabolic disturbance by regulating autophagy to a large extent. GLP-1 is thought to exert its functions through GLP-1R (Cai et al, 2017). To explore the receptor-dependent mechanism of liraglutide on erectile function, we examined the expression profiles of GLP-1R by immunohistochemistry in the corpus cavernosum of all groups.…”
Section: Discussionmentioning
confidence: 99%